Hubungan Antara Health Literacy Dengan Kepatuhan Mengkonsumsi Obat Antiretroviral Pada Orang Dengan HIV (ODHIV) - Rizsa Aulia Anindhita; Ahmad Ikhlasul Amal; Erna Melastuti (Protein : Jurnal Ilmu Keperawatan dan Kebidanan., 2025)
Human Immunodeficiency Virus (HIV) is a disease that attacks the body's immune system so that it is unable to fight various diseases. Communities with low levels of health literacy will face more problems. According to the Central Java Provincial Health Service, the number of HIV sufferers has also increased rapidly to Central Java, Semarang City with 331 cases, and the majority of those infected are men. The general aim of this research is to determine the relationship between health literacy and adherence to taking antiretroviral drugs (ARV) in people living with HIV (PLHIV). This research is a type of non-experimental descriptive analytical research with a cross-sectional approach. The samples taken were all patients with HIV (PLHIV) who took ARV drugs in the work area of ​​the Poncol Health Center, Semarang City. The technique used was consecutive sampling of 83 people. The correlation test used in this research is the chi-square test. From the results of the analysis, it was found that of the 83 research respondents, there was a relationship between the health literacy of people living with HIV (PLHIV) and the use of antiretroviral drugs (p value 0.003). The research results showed that the majority of respondents had high health literacy and were compliant with medication consumption with a total of 55 respondents (96.5%).